DISKRESI DAN POTENSI KORUPSI DALAM PENYELESAIAN MASALAH HUKUM TERKAIT PERCEPATAN PELAKSANAAN PROYEK STRATEGIS NASIONAL (ANALISIS TERHADAP PERATURAN PRESIDEN NOMOR 3 TAHUN 2016 DAN INSTRUKSI PRESIDEN NOMOR 1 TAHUN 2016) - Syawawi, Reza (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum dan Hak Asasi Manusia, 2021)
National strategic project is part of Jokowi’s economic program in his administration during his first and second term. This project is aimed to accelerate economic development through infrastructure projects. This project also expected to give impact to the improvement of public services and social welfare. President regelation (Peraturan Presiden) No. 3 Year 2016 and President Instruction (Instruksi Presiden) No. 1 Year 2016 also aimed to accelerate national strategic program such as in giving discretion in solving legal dispute. The president order police and attorney to report abuse of power in national strategic program in another institution to be solved administratively instead of take investigation about the report. This regulation clearly violate the principle of anti corruption act. The Law of Eradication of Corruption clearly mention that there is public right to report and to get information about the progress of any cases. If the police and the attorney only follow up the report to the another institution then it means it is not comply with the law. Even in the criminal law (KUHAP) is mentioned that any report from the public, the law enforcers should investigate the report, not just sending it to another institution. So the discretion in the Perpres and Inpres already loose its relevance with the regulation in the law of administrative governance. Discretion ideally can not violate the law and regulation. If the law enforcer are has any options to do some discretion then it should be done tightly. law enforcement should not be assumed as obstacle in development, but it should be a trigger to a better development.